A novel c.952T>C mutation in Notch3 gene in a patient with chronic non‐migraine‐like headache: Expanding the genotypic spectrum of CADASIL?. Issue 1 (11th April 2022) - Scala, Irene; Piane, Maria; Frisullo, Giovanni; Marotta, Jessica; Bellavia, Simone; Rizzo, Pier Andrea; Rollo, Eleonora; Vollono, Catello; Pizzuti, Antonio; Brunetti, Valerio; Della Marca, Giacomo
Abstract :